#### Answer

LHS $ = \lim\limits_{x \to 2} (x^{2} - 3x ) $
$ = 2^{2} - 3(2)$
$ = 4 - 6 $
$ = -2 $
= RHS

#### Work Step by Step

Simply substitute 2 into the function.

Published by
Cengage Learning

ISBN 10:
1285741552

ISBN 13:
978-1-28574-155-0

LHS $ = \lim\limits_{x \to 2} (x^{2} - 3x ) $
$ = 2^{2} - 3(2)$
$ = 4 - 6 $
$ = -2 $
= RHS

Simply substitute 2 into the function.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.